Composite negative electrode material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202611257771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
主要不足之处如下:1)硅颗粒易团聚,与碳源分散不均:原始硅颗粒表面与碳源材料表面均带负电,因同性相斥作用,直接混合时硅颗粒难以均匀分散在碳基体中,易出现团聚现象,且会产生大量未复合的自由硅颗粒,充放电过程中团聚的硅颗粒会加剧体积效应,导致材料粉化脱落
(1)本发明通过EDTA对硅颗粒进行表面修饰,使其表面电荷由负转正,实现了硅颗粒在碳基体中的均匀分散,避免团聚及自由硅颗粒的产生,同时EDTA诱导的纳米化效应显著降低了硅体积膨胀产生的应变;氮掺杂碳基体提升了材料导电性和储锂活性位点,弥补了硅的本征缺陷;在均匀分散的纳米硅颗粒与氮掺杂碳基体的协同配合下,不仅为硅的体积变化提供充足缓冲空间,有效抑制硅颗粒的裂痕与粉化,确保了材料结构稳定性,而且能够避免新表面持续暴露,促进形成稳定、薄且致密的SEI膜,减少锂离子与电解液的消耗;特别地,EDTA的桥接作用增强了硅颗粒与碳基体之间的结合力,形成稳定的复合结构,能避免充放电过程中的界面分离,保障离子与电子的连续传输。因此,该复合负极材料展现出优异的循环稳定性和倍率性能,能够满足高容量锂离子电池的应用需求。
Smart Images

Figure CN122930879A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to a composite negative electrode material, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries, as a new generation of green energy storage devices, are widely used in portable electronic devices, electric vehicles, and large-scale energy storage systems due to their advantages such as high energy density, long cycle life, and no memory effect. The anode material is the core component that determines the energy density and cycle performance of lithium-ion batteries. Currently, the theoretical specific capacity of commercially available graphite anodes is only 372 mAh / g, which is insufficient to meet the development needs of high-capacity lithium-ion batteries.
[0003] Silicon-based materials have an extremely high theoretical specific capacity (Li). 15 With its theoretical specific capacity of 3579 mAh / g, abundant reserves in the Earth's crust, environmental friendliness, and low operating potential, Si4 has become one of the most promising high-capacity anode materials to replace graphite. The lithium storage mechanism of silicon-based materials is an alloying reaction, where reversible alloying / dealloying reactions with lithium ions achieve lithium ion storage and release. However, pure silicon-based materials have inherent defects that limit their commercial application. Therefore, current technologies often employ silicon-carbon composites to modify silicon-based materials, utilizing the good conductivity, mechanical flexibility, and structural stability of carbon materials to alleviate the volume effect of silicon and improve the electrochemical performance of silicon-based anodes.
[0004] Currently, the main technologies for preparing silicon-carbon composite anode materials include physical mixing of nano-silicon particles and carbon materials, carbon layer coating of nano-silicon, and embedding silicon particles into a porous carbon framework. Some technologies further optimize material performance by surface modification of silicon particles or heteroatom doping of the carbon matrix.
[0005] However, existing silicon-carbon composite technologies have not fundamentally solved the core problems of silicon-based materials, and there are still many areas for optimization in terms of preparation processes and material properties, preventing large-scale industrial application. The main shortcomings are as follows: 1) Silicon particles are prone to agglomeration and uneven dispersion with the carbon source: Both the surface of the original silicon particles and the surface of the carbon source material are negatively charged. Due to the repulsion of like charges, it is difficult for silicon particles to be uniformly dispersed in the carbon matrix during direct mixing, easily leading to agglomeration and the generation of a large number of uncomposite free silicon particles. During charging and discharging, the agglomerated silicon particles exacerbate the volume effect, causing the material to pulverize and detach. 2) The volume effect is not effectively suppressed: When silicon undergoes an alloying reaction with lithium ions, the volume expansion rate is as high as 290%~320%. In existing silicon-carbon composite materials, the silicon particles are large in size or poorly dispersed, and the buffering effect of the carbon matrix is limited. During charging and discharging, silicon particles are prone to cracking and pulverization, losing electrical contact with the current collector, leading to rapid capacity decay. 3) Poor electrical conductivity and electrochemical kinetics: The room temperature conductivity of pure silicon is only <10-3 S / cm, and the lithium-ion diffusion coefficient is as low as 10. -14 ~10 -13 cm 2 4) Unstable Solid Electrolyte (SEI): Silicon particle pulverization exposes new surfaces, leading to continuous irreversible reactions with the electrolyte. This repeatedly forms a thick and unstable SEI film, consuming large amounts of lithium ions and electrolyte, increasing the battery's charge transfer resistance, and further exacerbating capacity decay. 5) Defects in the preparation process: Some existing silicon-carbon composite preparation technologies require expensive templates, surfactants, or complex equipment (such as vapor deposition equipment). The preparation steps are cumbersome, and the reaction conditions are harsh. Some technologies have complex surface modification methods, high-cost modifiers, poor product repeatability, and low raw material utilization, making it difficult to achieve large-scale industrial production. 6) Poor interfacial compatibility: The bonding force between silicon and carbon matrix in existing silicon-carbon composite materials is weak, and interfacial separation is prone to occur during charge and discharge, which leads to the disruption of ion and electron transport paths, increased charge transfer resistance, and further reduction in the cycle stability and rate performance of the material.
[0006] Therefore, how to simultaneously solve problems such as poor silicon particle dispersion, significant volume effect, insufficient conductivity, unstable SEI film and poor interface compatibility is a key research direction in this field. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a composite anode material, its preparation method, and a lithium-ion battery. This invention utilizes EDTA (ethylenediaminetetraacetic acid) to modify the surface of silicon particles, transforming their surface charge from negative to positive. This achieves uniform dispersion of silicon particles within a carbon matrix, preventing agglomeration and the formation of free silicon particles. Simultaneously, the EDTA-induced nano-sizing effect significantly reduces strain caused by silicon volume expansion. Nitrogen-doped carbon matrix enhances the material's conductivity and lithium storage active sites, compensating for intrinsic silicon defects. The synergistic effect of uniformly dispersed nano-silicon particles and nitrogen-doped carbon matrix not only provides ample buffer space for silicon volume changes, effectively suppressing silicon particle cracking and pulverization, ensuring material structural stability, but also prevents continuous exposure of new surfaces, promoting the formation of a stable, thin, and dense SEI film, and reducing lithium ion and electrolyte consumption. In particular, the bridging effect of EDTA enhances the bonding force between silicon particles and the carbon matrix, forming a stable composite structure that avoids interfacial separation during charging and discharging, ensuring continuous ion and electron transport. Therefore, this composite anode material exhibits excellent cycle stability and rate performance, which can meet the application requirements of high-capacity lithium-ion batteries.
[0008] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a composite anode material comprising nano-silicon particles with EDTA surface-modified and a nitrogen-doped carbon matrix.
[0009] The nano-silicon particles are bonded to the nitrogen-doped carbon matrix through the bridging effect of the EDTA; the doped nitrogen in the nitrogen-doped carbon matrix is provided by the pyrolysis of the EDTA.
[0010] This invention modifies the surface of silicon particles with EDTA, changing their surface charge from negative to positive, thus achieving uniform dispersion of silicon particles in a carbon matrix and avoiding agglomeration and the formation of free silicon particles. Simultaneously, the EDTA-induced nano-sizing effect significantly reduces strain caused by silicon volume expansion. The nitrogen-doped carbon matrix enhances the material's conductivity and lithium storage active sites, compensating for the intrinsic defects of silicon. The synergistic effect of the uniformly dispersed nano-silicon particles and the nitrogen-doped carbon matrix not only provides ample buffer space for silicon volume changes, effectively suppressing silicon particle cracking and pulverization and ensuring material structural stability, but also prevents continuous exposure of new surfaces, promoting the formation of a stable, thin, and dense SEI film and reducing lithium ion and electrolyte consumption. In particular, the bridging effect of EDTA enhances the bonding force between silicon particles and the carbon matrix, forming a stable composite structure that avoids interfacial separation during charging and discharging, ensuring continuous ion and electron transport. Therefore, this composite anode material exhibits excellent cycle stability and rate performance, and can replace graphite anodes in various high-capacity lithium-ion batteries. It has broad industrial application prospects and market value in portable electronic devices, electric vehicles, large-scale energy storage systems and other fields.
[0011] Preferably, the surface charge of the nano-silicon particles is positive.
[0012] This invention modifies the surface of silicon particles with EDTA, achieving both nano-refinement of silicon particles and charge reversal, with the surface charge changing from negative to positive. This solves the problems of isotropic repulsion between silicon particles and carbon source surfaces, uneven dispersion, and easy agglomeration in existing silicon-carbon composite materials, achieving uniform dispersion of silicon particles in the carbon matrix and eliminating free silicon particles.
[0013] Preferably, the particle size D100 of the nano-silicon particles is ≤40nm, for example, it can be 20nm, 25nm, 30nm, 35nm or 40nm, etc.
[0014] This invention achieves a silicon particle size D100≤40nm through EDTA modification, and in synergy with the nitrogen-doped carbon matrix, provides sufficient buffer space for silicon volume expansion, effectively suppressing silicon particle cracking and pulverization.
[0015] Preferably, the type of nitrogen dopant includes pyrrole N and / or graphite N.
[0016] This invention utilizes nitrogen provided by EDTA pyrolysis to dope a carbon matrix, where it exists in the form of pyrrole N and / or graphite N, introducing a large number of lithium storage active sites and optimizing the electronic structure of the carbon matrix, thereby improving the conductivity of the material.
[0017] Preferably, based on the total mass of the composite negative electrode material, the mass content of the EDTA-modified nano-silicon particles is 15-45 wt%, for example, it can be 15 wt%, 17.4 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, or 45 wt%.
[0018] In this invention, the appropriate mass content of EDTA-modified nano-silicon particles can effectively solve the problems of isotropic repulsion between silicon particles and carbon source surfaces, uneven dispersion, and easy agglomeration in existing silicon-carbon composite materials while achieving nano-refinement of silicon particles. This enables uniform dispersion of silicon particles in the carbon matrix and eliminates free silicon particles.
[0019] Preferably, in the nitrogen-doped carbon matrix, the amount of nitrogen doping is 0.5-2.1 at.%, for example, it can be 0.5 at.%, 1.0 at.%, 1.5 at.%, 2.0 at.%, or 2.1 at.%.
[0020] The nitrogen-doped carbon matrix provided by this invention has a suitable amount of nitrogen doping, which can fully introduce a large number of lithium storage active sites, while optimizing the electronic structure of the carbon matrix and significantly improving the conductivity of the material.
[0021] Preferably, the composite anode material has a core-shell structure, with the core being the nano-silicon particles and the outer shell being the nitrogen-doped carbon matrix. It should be noted that the core-shell structure of the composite anode material means that the nitrogen-doped carbon matrix, as a continuous phase, completely encapsulates the core composed of nano-silicon particles. The core can be a single nano-silicon particle or a cluster of multiple nano-silicon particles. The nitrogen-doped carbon matrix of the continuous phase has a uniform or nearly uniform thickness, completely encapsulating the core and forming a stable core-shell composite structure.
[0022] In this invention, the composite negative electrode material has a core-shell structure, which can effectively isolate the direct contact between silicon particles and electrolyte, and promote the formation of a stable SEI film.
[0023] In a second aspect, the present invention provides a method for preparing the composite anode material as described in the first aspect, the method comprising the following steps: The original silicon particles and EDTA liquid phase were mixed and subjected to a surface modification reaction to obtain a Si-EDTA composite.
[0024] The Si-EDTA composite and a carbon source precursor are mixed and pyrolyzed to carbonize the carbon source precursor and achieve nitrogen doping. At the same time, the nano-silicon particles are bonded to the carbon matrix through the bridging effect of EDTA to obtain the composite anode material.
[0025] The preparation method provided by this invention uses inexpensive and readily available raw materials, has a simple and easy-to-operate process, mild reaction conditions, good product repeatability, and produces no toxic or harmful byproducts during production, which meets the requirements of green chemistry. In addition, the raw material utilization rate is high, which greatly reduces the production cost and makes it easy to achieve large-scale industrial production. It has broad prospects for industrial application.
[0026] Preferably, the particle size D50 of the original silicon particles is 450-550nm, for example, it can be 450nm, 500nm or 550nm, etc.
[0027] Preferably, the mass ratio of the raw silicon particles to EDTA is 1:(0.5-2), for example, it can be 1:0.5, 1:1, 1:1.5 or 1:2, etc.
[0028] Preferably, the surface modification reaction is carried out at room temperature for 12-24 hours, such as 12 hours, 16 hours, 20 hours, or 24 hours. It should be noted that the specific room temperature is not limited in this invention, but is typically 20-30°C, such as 20°C, 25°C, or 30°C.
[0029] Preferably, the surface modification reaction is accompanied by stirring.
[0030] Preferably, the carbon source precursor includes any one or a combination of at least two of coal tar pitch, pitch coke, or phenolic resin.
[0031] Preferably, the mass ratio of the Si-EDTA composite to the carbon source precursor is 1:(1-3), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, etc.
[0032] Preferably, the atmosphere for pyrolysis is an inert atmosphere. Examples include nitrogen or argon.
[0033] Preferably, the pyrolysis temperature is 800-1000℃, for example, it can be 800℃, 850℃, 900℃, 950℃ or 1000℃.
[0034] In this invention, since EDTA is both a modifier and dispersant for silicon and a nitrogen doping source for the silicon matrix, at a suitable pyrolysis temperature, EDTA thermally decomposes to release N active species, and the carbon source precursor simultaneously forms a carbon matrix. N atoms replace C in situ or embed into defect sites to form pyrrole N and graphite N, thus completing nitrogen doping. This is beneficial for the nitrogen doping to provide additional active Li storage sites for the material, and can also improve the ion and electron transport capabilities of the material.
[0035] Preferably, the pyrolysis time is 2-3 hours, for example, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours or 3 hours.
[0036] Preferably, the preparation method includes the following steps: (1) Add raw silicon particles with a particle size D50 of 450-550nm and EDTA to water at a mass ratio of 1:(0.5-2) to obtain a mixed solution with a solid-liquid ratio of 1g:(20-100)mL (for example, it can be 1g:20mL, 1g:30mL, 1g:40mL, 1g:50mL, 1g:60mL, 1g:70mL, 1g:80mL, 1g:90mL or 1g:100mL, etc.).
[0037] The mixed solution was placed at room temperature and magnetically stirred for 12-24 hours to carry out the surface modification reaction. Then, it was centrifuged at 8000-12000 rpm (e.g., 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, or 12000 rpm) for 5-10 minutes (e.g., 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes) and the solid precipitate was collected.
[0038] The solid precipitate was washed and dried to obtain the Si-EDTA complex.
[0039] (2) The Si-EDTA composite and the carbon source precursor are dry ball-milled at a mass ratio of 1:(1-3) to obtain a mixture with a particle size of <100 mesh (e.g., 90 mesh, 80 mesh or 70 mesh).
[0040] Under an inert atmosphere, the temperature is increased to 800-1000℃ at a heating rate of 2-5℃ / min (e.g., 2℃ / min, 3℃ / min, 4℃ / min, or 5℃ / min, etc.) and pyrolyzed for 2-3 hours, so that the carbon source precursor is carbonized and nitrogen doped. At the same time, the nano-silicon particles are bonded to the carbon matrix through the bridging effect of EDTA. Then, the material is cooled to obtain the composite anode material.
[0041] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising the composite negative electrode material as described in the first aspect.
[0042] For example, the preparation method of the negative electrode sheet is as follows: a composite negative electrode material, a conductive agent and a binder are mixed and added to an organic solvent to obtain a negative electrode slurry; the negative electrode slurry is coated on a current collector, dried and rolled to obtain a negative electrode sheet.
[0043] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising the negative electrode sheet as described in the third aspect.
[0044] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0045] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention modifies the surface of silicon particles with EDTA, changing the surface charge from negative to positive, thus achieving uniform dispersion of silicon particles in the carbon matrix and avoiding agglomeration and the generation of free silicon particles. At the same time, the nano-sizing effect induced by EDTA significantly reduces the strain caused by silicon volume expansion. The nitrogen-doped carbon matrix improves the conductivity and lithium storage active sites of the material, compensating for the intrinsic defects of silicon. With the synergistic effect of uniformly dispersed nano-silicon particles and nitrogen-doped carbon matrix, not only is sufficient buffer space provided for silicon volume changes, effectively suppressing silicon particle cracking and pulverization and ensuring the stability of the material structure, but it can also avoid continuous exposure of new surfaces, promote the formation of a stable, thin and dense SEI film, and reduce the consumption of lithium ions and electrolyte. In particular, the bridging effect of EDTA enhances the bonding force between silicon particles and carbon matrix, forming a stable composite structure, which can avoid interface separation during charging and discharging and ensure the continuous transport of ions and electrons. Therefore, this composite anode material exhibits excellent cycle stability and rate performance, which can meet the application requirements of high-capacity lithium-ion batteries.
[0046] (2) The preparation method provided by the present invention uses inexpensive and readily available raw materials, simple and easy-to-operate process, mild reaction conditions, good product repeatability, no toxic and harmful by-products are generated during the production process, which meets the requirements of green chemical industry, and the raw material utilization rate is high, which greatly reduces the production cost, makes it easy to realize large-scale industrial production, and has broad industrial application prospects. Attached Figure Description
[0047] Figure 1 The image shows the zeta potential test results for the original silicon particles, coal tar pitch, and EDTA-modified nano-silicon particles provided in Example 1 of this application.
[0048] Figure 2 The XRD diffraction pattern is shown for the composite negative electrode material provided in Example 1 of this application.
[0049] Figure 3 The Raman test curve is shown for the composite negative electrode material provided in Example 1 of this application.
[0050] Figure 4 This is an AC impedance (EIS) test diagram of the composite negative electrode material provided in Example 1 of this application. Detailed Implementation
[0051] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0052] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0053] In this invention, "a combination of at least two" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or a combination of at least two" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention. In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this invention, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0054] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various locations throughout the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this invention can be combined with other embodiments that do not conflict with the technology. The ordinal numbers "first," "second," "third," and "fourth," etc., used in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect" in this invention are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0055] In this invention, the order in which the steps are written in the methods described in each embodiment does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0056] It should be noted that the room temperature mentioned below refers to 25℃.
[0057] Example 1 This embodiment provides a composite anode material, which includes nano-silicon particles with EDTA surface modified and a nitrogen-doped carbon matrix.
[0058] The nano-silicon particles are bonded to the nitrogen-doped carbon matrix through the bridging effect of the EDTA; the doped nitrogen in the nitrogen-doped carbon matrix is provided by the pyrolysis of the EDTA.
[0059] The nano-silicon particles have a positive surface charge; the particle size D100 of the nano-silicon particles is ≤40nm; the type of nitrogen dopant includes pyrrole N and graphite N; based on the total mass of the composite anode material, the mass content of the EDTA-modified nano-silicon particles is 17.4wt%; the nitrogen doping amount in the nitrogen-doped carbon matrix is 2.04 at.%; the composite anode material has a core-shell structure, with the nano-silicon particles as the core and the nitrogen-doped carbon matrix as the outer shell.
[0060] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps: (1) Add 5g of raw silicon particles with a particle size D50 of 500nm and 7.5g of EDTA to 500mL of deionized water at a mass ratio of 1:1.5 to obtain a mixed solution with a solid-liquid ratio of 1g:40mL.
[0061] The mixed solution was placed at room temperature and magnetically stirred for 18 hours to carry out the surface modification reaction, and then centrifuged at 10,000 rpm for 8 minutes to collect the solid precipitate.
[0062] The solid precipitate was washed three times alternately with deionized water and anhydrous ethanol, and then dried under vacuum at 70°C for 12 h to obtain the Si-EDTA complex.
[0063] (2) 5g of the Si-EDTA composite and 10g of coal tar pitch were placed in an agate mortar at a mass ratio of 1:2 and dry ball milled for 45 minutes to make the particle size <100 mesh, thus obtaining a mixture.
[0064] The mixture was placed in a tube furnace under a nitrogen atmosphere and heated from room temperature to 900°C at a rate of 3°C / min for 2.5 hours for pyrolysis. This process carbonized the carbon source precursor and achieved nitrogen doping. Simultaneously, the nano-silicon particles were bonded to the carbon matrix through the bridging effect of EDTA. After the tube furnace cooled naturally to room temperature, the product was collected to obtain the composite anode material.
[0065] Zeta potential testing was performed on this embodiment, such as... Figure 1As shown, the surfaces of the original silicon particles and coal tar pitch were found to be negatively charged, while the surface charge of the nano-silicon particles modified with EDTA changed from negative to positive.
[0066] The composite anode material provided in this embodiment was subjected to SEM and TEM tests, which showed that the composite anode material contains nano-silicon particles with a particle size of 20-40 nm, which are uniformly dispersed in a nitrogen-doped carbon matrix without agglomeration, cracks and free silicon particles, and the carbon matrix forms a tight coating on the nano-silicon.
[0067] XRD tests were performed on the composite anode material provided in this embodiment, such as... Figure 2 As shown, the test results show that the composite anode material exhibits characteristic diffraction peaks of silicon at positions such as 2θ=28.2° and 47.1°, and a broad peak of amorphous carbon at 2θ≈25°, proving that the silicon-carbon composite was successful.
[0068] The composite anode material provided in this embodiment was subjected to Raman testing, such as... Figure 3 As shown, the test results indicate that the ID / IG ratio of the composite anode material is greater than 1, and the carbon matrix has a large number of defects, providing abundant active sites for lithium storage.
[0069] XPS testing was performed on the composite anode material provided in this embodiment. The test results showed that nitrogen was doped into the carbon framework in the form of pyrrole N (399.4 eV) and graphite N (401.4 eV). The silicon, carbon, nitrogen and oxygen elements were evenly distributed, proving that nitrogen doping was successful.
[0070] The composite negative electrode material, conductive carbon black (Super P), and polyvinylidene fluoride provided in this embodiment are mixed at a mass ratio of 8:1:1, and then added to N-methylpyrrolidone (NMP). The mixture is magnetically stirred until a uniform and viscous negative electrode slurry is formed. The negative electrode slurry is uniformly coated onto a copper foil current collector and dried in a vacuum drying oven at 60°C for 12 hours. The slurry is then rolled using a roller press (area density 1.5 mg / cm³). 2 After being stamped into a 12mm diameter disc, it is made into a negative electrode. The negative electrode is used as the working electrode, the lithium sheet is used as the counter electrode, Celgard2400 is used as the separator, and 1mol / L LiPF6 EC / DMC / EMC (volume ratio 1:1:1) is used as the electrolyte. The CR2032 coin cell is assembled in an argon glove box.
[0071] The CR2032 coin cell lithium half-cell was subjected to AC impedance (EIS) testing under a constant temperature of 25℃. Figure 4 As shown in the figure, the test results show that, compared with pure silicon anode materials, the composite anode material provided in this embodiment has low charge transfer resistance, high lithium-ion diffusion coefficient, and good electrochemical kinetic performance.
[0072] Cyclic voltammetry (CV) tests were conducted on the CR2032 coin-type lithium half-cell. The test results showed that the composite anode material provided in this embodiment formed a stable redox peak after the first charge and discharge, and the subsequent cycle curves almost overlapped, proving that the reaction has good reversibility and the SEI film is stable.
[0073] Example 2 This embodiment provides a composite anode material, which includes nano-silicon particles with EDTA surface modified and a nitrogen-doped carbon matrix.
[0074] The nano-silicon particles are bonded to the nitrogen-doped carbon matrix through the bridging effect of the EDTA; the doped nitrogen in the nitrogen-doped carbon matrix is provided by the pyrolysis of the EDTA.
[0075] The nano-silicon particles have a positive surface charge; the particle size D100 of the nano-silicon particles is ≤40nm; the type of nitrogen dopant includes pyrrole N and graphite N; based on the total mass of the composite anode material, the mass content of the EDTA-modified nano-silicon particles is 17.4wt%; the nitrogen doping amount in the nitrogen-doped carbon matrix is 2.04 at.%; the composite anode material has a core-shell structure, with the nano-silicon particles as the core and the nitrogen-doped carbon matrix as the outer shell.
[0076] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps: (1) Add 5g of raw silicon particles with a particle size D50 of 500nm and 5g of EDTA to 400mL of deionized water at a mass ratio of 1:1 to obtain a mixed solution with a solid-liquid ratio of 1g:40mL.
[0077] The mixed solution was placed at room temperature and magnetically stirred for 24 hours to carry out the surface modification reaction, and then centrifuged at 12,000 rpm for 5 minutes to collect the solid precipitate.
[0078] The solid precipitate was washed twice alternately with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 10 h to obtain the Si-EDTA composite.
[0079] (2) 5g of the Si-EDTA composite and 7.5g of phenolic resin were placed in an agate mortar at a mass ratio of 1:1.5 and dry ball milled for 30min to make the particle size <100 mesh, thus obtaining a mixture.
[0080] The mixture was placed in a tube furnace under a nitrogen atmosphere and heated from room temperature to 850°C at a heating rate of 5°C / min for 3 hours for pyrolysis. This process carbonized the carbon source precursor and achieved nitrogen doping. Simultaneously, the nano-silicon particles were bonded to the carbon matrix through the bridging effect of EDTA. After the tube furnace cooled naturally to room temperature, the product was collected to obtain the composite anode material.
[0081] Example 3 This embodiment provides a composite anode material, which includes nano-silicon particles with EDTA surface modified and a nitrogen-doped carbon matrix.
[0082] The nano-silicon particles are bonded to the nitrogen-doped carbon matrix through the bridging effect of the EDTA; the doped nitrogen in the nitrogen-doped carbon matrix is provided by the pyrolysis of the EDTA.
[0083] The nano-silicon particles have a positive surface charge; the particle size D100 of the nano-silicon particles is ≤40nm; the type of nitrogen dopant includes pyrrole N and graphite N; based on the total mass of the composite anode material, the mass content of the EDTA-modified nano-silicon particles is 17.4wt%; the nitrogen doping amount in the nitrogen-doped carbon matrix is 2.04 at.%; the composite anode material has a core-shell structure, with the nano-silicon particles as the core and the nitrogen-doped carbon matrix as the outer shell.
[0084] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps: (1) Add 5g of raw silicon particles with a particle size D50 of 500nm and 10g of EDTA to 400mL of deionized water at a mass ratio of 1:2 to obtain a mixed solution with a solid-liquid ratio of 3g:80mL.
[0085] The mixed solution was placed at room temperature and magnetically stirred for 12 h to carry out the surface modification reaction, and then centrifuged at 8000 rpm for 10 min to collect the solid precipitate.
[0086] The solid precipitate was washed three times alternately with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 10 h to obtain the Si-EDTA composite.
[0087] (2) 5g of the Si-EDTA composite and 15g of coal tar pitch were placed in an agate mortar at a mass ratio of 1:3 and dry ball milled for 50 minutes to make the particle size <100 mesh, thus obtaining the mixture.
[0088] The mixture was placed in a tube furnace under a nitrogen atmosphere and heated from room temperature to 1000°C at a heating rate of 5°C / min for 2 hours for pyrolysis. This carbonized the carbon source precursor and achieved nitrogen doping. At the same time, the nano-silicon particles were bonded to the carbon matrix through the bridging effect of EDTA. After the tube furnace cooled naturally to room temperature, the product was collected to obtain the composite anode material.
[0089] Example 4 The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the original silicon particles to EDTA is 1:0.5.
[0090] The remaining preparation methods and parameters are consistent with those in Example 1.
[0091] Example 5 The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of the original silicon particles to EDTA is 1:1.
[0092] The remaining preparation methods and parameters are consistent with those in Example 1.
[0093] Example 6 The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of raw silicon particles to EDTA is 1:2.
[0094] The remaining preparation methods and parameters are consistent with those in Example 1.
[0095] Example 7 The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of raw silicon particles to EDTA is 1:2.5.
[0096] The remaining preparation methods and parameters are consistent with those in Example 1.
[0097] Example 8 The difference between this embodiment and embodiment 1 is that in step (1), the mass ratio of raw silicon particles to EDTA is 1:0.3.
[0098] The remaining preparation methods and parameters are consistent with those in Example 1.
[0099] Example 9 The difference between this embodiment and Embodiment 1 is that the mass ratio of the Si-EDTA composite and coal tar pitch is adjusted so that the nitrogen doping amount in the nitrogen-doped carbon matrix is 0.1 at.%. The remaining preparation methods and parameters are the same as in Embodiment 1.
[0100] Example 10 The difference between this embodiment and Embodiment 1 is that the mass ratio of the Si-EDTA composite and coal tar pitch is adjusted so that the amount of nitrogen doped in the nitrogen-doped carbon matrix is 10 at.
[0101] The remaining preparation methods and parameters are consistent with those in Example 1.
[0102] Example 11 The difference between this embodiment and embodiment 1 is that the pyrolysis temperature in step (2) is 700℃.
[0103] The remaining preparation methods and parameters are consistent with those in Example 1.
[0104] Example 12 The difference between this embodiment and embodiment 1 is that the pyrolysis temperature in step (2) is 1100℃.
[0105] The remaining preparation methods and parameters are consistent with those in Example 1.
[0106] Comparative Example 1 The difference between this comparative example and Example 1 is that EDTA is not added in step (1).
[0107] The remaining preparation methods and parameters are consistent with those in Example 1.
[0108] Comparative Example 2 This comparative example provides a method for preparing a composite anode material, including the following steps: (1) Place 0.2g of nano-silicon powder into 30mL of ethanol, disperse it by ultrasonication, add 20mL of 1mol / L sodium persulfate solution and stir at 0℃ for 0.5h to obtain dispersion A; the particle size of the nano-silicon powder is 30nm.
[0109] (2) Add 500 μL of pyrrole to the dispersion A obtained in step (1), stir and mix, and react at 0°C for 5 h. Filter and wash the obtained solid with ethanol and water, and dry it at 60°C to obtain precursor B.
[0110] (3) The precursor B obtained in step (2) is calcined at 800℃ for 3 hours and then cooled to obtain the composite anode material.
[0111] Performance testing Based on the composite negative electrode material provided in the above embodiments and comparative examples, a negative electrode sheet is prepared and assembled into a CR2032 type coin cell lithium half-cell. The steps include: Composite negative electrode material, conductive carbon black (Super P), and polyvinylidene fluoride were mixed at a mass ratio of 8:1:1, and then added to N-methylpyrrolidone (NMP). The mixture was magnetically stirred until a uniform and viscous negative electrode slurry was formed. The negative electrode slurry was uniformly coated onto a copper foil current collector and dried in a vacuum drying oven at 60°C for 12 hours. The slurry was then rolled using a roller press (area density 1.5 mg / cm³). 2 After being stamped into a 12mm diameter disc, it is made into a negative electrode. The negative electrode is used as the working electrode, the lithium sheet is used as the counter electrode, Celgard2400 is used as the separator, and 1mol / L LiPF6 EC / DMC / EMC (volume ratio 1:1:1) is used as the electrolyte. The CR2032 coin cell is assembled in an argon glove box.
[0112] Electrochemical performance tests were conducted on CR2032 coin cell lithium half-cells under a constant temperature of 25℃, including: Cycling performance: The reversible specific capacity and corresponding coulombic efficiency of the battery were measured after 130 cycles at a current density of 200 mA / g.
[0113] Rate performance: Charge-discharge cycles were performed sequentially at current densities of 100 mA / g, 500 mA / g, 1000 mA / g, and 2000 mA / g, with 5 charge-discharge cycles at each current density; the discharge specific capacity at each current density was recorded, and the capacity retention rate at 1000 mA / g was also recorded.
[0114] The results are shown in Table 1.
[0115] Table 1 analyze: As shown in Table 1, this invention modifies the surface of silicon particles with EDTA (ethylenediaminetetraacetic acid), changing the surface charge from negative to positive. This achieves uniform dispersion of silicon particles in the carbon matrix, avoiding agglomeration and the formation of free silicon particles. Simultaneously, the EDTA-induced nano-sizing effect significantly reduces strain caused by silicon volume expansion. The nitrogen-doped carbon matrix enhances the material's conductivity and lithium storage active sites, compensating for the intrinsic defects of silicon. The synergistic effect of the uniformly dispersed nano-silicon particles and the nitrogen-doped carbon matrix not only provides sufficient buffer space for silicon volume changes, effectively suppressing silicon particle cracking and pulverization and ensuring material structural stability, but also prevents continuous exposure of new surfaces, promoting the formation of a stable, thin, and dense SEI film, reducing lithium ion and electrolyte consumption. In particular, the bridging effect of EDTA enhances the bonding force between silicon particles and the carbon matrix, forming a stable composite structure that avoids interface separation during charging and discharging, ensuring continuous ion and electron transport. Therefore, this composite anode material exhibits excellent cycle stability and rate performance, meeting the application requirements of high-capacity lithium-ion batteries.
[0116] As can be seen from the comparison between Examples 1 and Examples 4-8, when the mass ratio of the original silicon particles to EDTA is within the protection range, the surface modification of the silicon particles is sufficient, the negative charge on the surface is sufficiently converted to positive, and they are uniformly dispersed in the carbon matrix, resulting in excellent electrochemical performance. However, when the mass ratio of the original silicon particles to EDTA is too small (as in Example 7), excessive EDTA is added, and unreacted EDTA will remain and affect the conductivity of the material, leading to a decrease in electrochemical performance. When the mass ratio of the original silicon particles to EDTA is too large (as in Example 8), the amount of EDTA added is insufficient, the surface modification of the silicon particles is insufficient, the charge is not completely reversed, and there is still slight agglomeration, which leads to and generates a large number of uncomposite free silicon particles. During the charging and discharging process, the agglomerated silicon particles will aggravate the volume effect, leading to the pulverization and shedding of the material.
[0117] A comparison of Examples 1 and 9-10 shows that if the amount of nitrogen doping in the nitrogen-doped carbon matrix is too low, there are insufficient active polar sites on the carbon matrix surface, resulting in fewer pseudocapacitive lithium storage sites and a limited increase in the specific capacity of the composite material. Although a lower heteroatom defect density can reduce irreversible lithium-ion capture and achieve a relatively high initial coulombic efficiency, the overall lithium storage capacity, rate performance, and cycle stability are inferior to those of moderately doped samples. If the amount of nitrogen doping in the nitrogen-doped carbon matrix is too high, excessive nitrogen doping will cause carbon lattice distortion, a large amount of irreversible lithium capture, and a reduction in initial coulombic efficiency; it will also damage the carbon conductive network, deteriorating rate performance; increase the number of polar active sites, catalyzing the continuous decomposition of the electrolyte; and weaken the mechanical stability of the carbon skeleton, making it difficult to buffer the volume expansion of lithium intercalation in tin-based materials, ultimately leading to a decline in cycle life and a continuous increase in interfacial impedance.
[0118] As can be seen from the comparison between Example 1 and Examples 11-12, if the pyrolysis temperature is too low, the carbonization is incomplete, the carbon skeleton is not fully formed, and the intrinsic conductivity is extremely poor; if the pyrolysis temperature is too high, the carbon matrix is excessively graphitized, the lithium storage capacity decreases significantly, a large number of disorder defects in the carbon material disappear, the contribution of defect adsorption lithium storage and pseudocapacitive lithium storage basically disappears, and the overall capacity limit of the composite material is reduced.
[0119] As can be seen from the comparison between Example 1 and Comparative Example 1, if EDTA is not added, the nano-Si particles will be difficult to mix fully with pitch carbon due to the repulsion of surface charges.
[0120] As can be seen from the comparison between Example 1 and Comparative Example 2, if the composite anode material is prepared using the process shown in Comparative Example 2, the initial coulombic efficiency is low, the pre-agglomeration of silicon particles easily leads to uneven coating, the locally exposed silicon surface will cause continuous SEI growth and electrolyte consumption, and the cycle impedance will gradually increase.
[0121] It should be noted that the present invention is illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite negative electrode material, characterized in that, The composite anode material comprises nano-silicon particles with EDTA surface-modified and a nitrogen-doped carbon matrix; The nano-silicon particles are bonded to the nitrogen-doped carbon matrix through the bridging effect of the EDTA; the doped nitrogen in the nitrogen-doped carbon matrix is provided by the pyrolysis of the EDTA.
2. The composite negative electrode material according to claim 1, characterized in that, The surface charge of the nano-silicon particles is positive. And / or, the particle size D100 of the said silicon nanoparticles is ≤40nm; And / or, the type of doped nitrogen includes pyrrole N and / or graphite N.
3. The composite negative electrode material according to claim 1 or 2, characterized in that, Based on the total mass of the composite anode material, the mass content of the EDTA-modified nano-silicon particles is 15-45 wt%. And / or, in the nitrogen-doped carbon matrix, the amount of nitrogen doped is 0.5-2.1 at.%.
4. The composite negative electrode material according to any one of claims 1-3, characterized in that, The composite anode material has a core-shell structure, with the core being the nano-silicon particles and the outer shell being the nitrogen-doped carbon matrix.
5. A method for preparing the composite negative electrode material according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: The original silicon particles and EDTA liquid phase were mixed and a surface modification reaction was carried out to obtain a Si-EDTA composite. The Si-EDTA composite and a carbon source precursor are mixed and pyrolyzed to carbonize the carbon source precursor and achieve nitrogen doping. At the same time, the nano-silicon particles are bonded to the carbon matrix through the bridging effect of EDTA to obtain the composite anode material.
6. The preparation method according to claim 5, characterized in that, The particle size D50 of the original silicon particles is 450-550 nm; And / or, the mass ratio of the raw silicon particles to EDTA is 1:(0.5-2); And / or, during the surface modification reaction, the temperature is room temperature and the time is 12-24 hours; And / or, the surface modification reaction is accompanied by stirring.
7. The preparation method according to claim 5 or 6, characterized in that, The carbon source precursor includes any one or a combination of at least two of coal tar pitch, pitch coke, or phenolic resin. And / or, the mass ratio of the Si-EDTA composite to the carbon source precursor is 1:(1-3); And / or, the atmosphere for pyrolysis is an inert atmosphere; And / or, the pyrolysis temperature is 800-1000℃; And / or, the pyrolysis time is 2-3 hours.
8. The preparation method according to any one of claims 5-7, characterized in that, The preparation method includes the following steps: (1) Add raw silicon particles with a particle size D50 of 450-550nm and EDTA to water at a mass ratio of 1:(0.5-2) to obtain a mixed solution with a solid-liquid ratio of 1g:(20-100)mL; The mixed solution was placed at room temperature and magnetically stirred for 12-24 hours to carry out the surface modification reaction, and then centrifuged at 8000-12000 rpm for 5-10 minutes to collect the solid precipitate. The solid precipitate was washed and dried to obtain the Si-EDTA complex; (2) The Si-EDTA composite and the carbon source precursor are dry ball-milled at a mass ratio of 1:(1-3) to obtain a mixture with a particle size of <100 mesh. Under an inert atmosphere, the temperature is increased to 800-1000℃ at a heating rate of 2-5℃ / min and pyrolyzed for 2-3 hours to carbonize the carbon source precursor and achieve nitrogen doping. At the same time, the nano-silicon particles are bonded to the carbon matrix through the bridging effect of EDTA. Then, the material is cooled to obtain a composite anode material.
9. A negative electrode sheet, characterized in that, The negative electrode sheet includes the composite negative electrode material as described in any one of claims 1-4.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the negative electrode sheet as described in claim 9.